The comparison of the effectiveness of self-compassion and Transactional Analysis on cognitive regulation of students' emotion with emotional failure experience - Dastmardi, Zahra; Moghtader, Leila; Akbari, Bahman (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the effectiveness of self-compassion in comparison with the effectiveness of Transactional Analysis on cognitive emotion regulation of students experiencing emotional failure. Methods: The present study was quasi-experimental with a pretest-posttest design and a two-month follow-up. The study statistical population included students with experience of emotional failure in Rasht Azad University in 2020, of which 45 students were selected by the convenience sampling method and randomly divided into three groups: self-compassion (15 people), Transactional Analysis (15 people), and the control group (15 people). The research tools included the emotion regulation questionnaire of Gross and John (2003). The students received the group therapy of Self-Compassion of Gilbert (2010) and the group therapy of Transactional Analysis of Conner et al. (2016) in eight sessions of 90-minute. The data were analyzed by using the repeated-measures analysis of variance. Results: The findings indicated that the intervention based on acceptance and commitment and Transactional Analysis was effective on emotional recovery (F = 4.55, P = 0.002) and emotional inhibition (F = 3.72, P = 0.009) of students with the experience of emotional failure. Also, the impact of both therapeutic approaches was stable until the follow-up stage (p < 0.05). There has been no difference obtained between the effectiveness of self-compassion compared to the treatment of Transactional Analysis in cognitive emotion regulation (p > 0.05). Conclusions: The obtained results indicated that there was no difference between the two methods of self-compassion and Transactional Analysis in terms of effectiveness. And both methods are appropriate ways to improve the level of cognitive emotion regulation of students with emotional failure experience.